Bradykinin receptor blockade restores the baroreflex control of renal sympathetic nerve activity in cisplatin‐induced renal failure rats. (29th September 2016) - Abdulla, M. H.; Duff, M.; Swanton, H.; Johns, E. J.
Abstract: Aim: This study investigated the effect of renal bradykinin B1 and B2 receptor blockade on the high‐ and low‐pressure baroreceptor reflex regulation of renal sympathetic nerve activity (RSNA) in rats with cisplatin‐induced renal failure. Methods: Cisplatin (5 mg/kg) or saline was given intraperitoneally 4 days prior to study. Following chloralose/urethane anaesthesia, rats were prepared for measurement of mean arterial pressure (MAP), heart rate and RSNA and received intrarenal infusions of either Lys‐[des‐Arg 9, Leu 8 ]‐bradykinin (LBK), a bradykinin B1 receptor blocker, or bradyzide (BZ), a bradykinin B2 receptor blocker. RSNA baroreflex gain curves and renal sympatho‐inhibitory responses to volume expansion (VE) were obtained. Results: In the control and renal failure groups, basal MAP (89 ± 3 vs. 80 ± 8 mmHg) and RSNA (2.0 ± 0.3 vs. 1.7 ± 0.6  μ V.s) were similar but HR was lower in the latter group (331 ± 8 vs. 396 ± 9 beats/min). The baroreflex gain for RSNA in the renal failure rats was 39% ( P  < 0.05) lower than the control but was restored to normal values following intrarenal infusion of BZ, but not LBK. VE had no effect on MAP or HR but reduced RSNA by some 40% ( P  < 0.05) in control but not renal failure rats. Intrarenal LBK infusion in the renal failure rats normalized the VE induced renal sympatho‐inhibition whereas BZ only partially restored the response. Conclusion: These findings suggest that pro‐inflammatory bradykinin acting at different receptors within the kidney generates afferent neural signals which impact differentially within the central nervous system on high‐ and low‐pressure regulation of RSNA.